2016
DOI: 10.1108/jpif-03-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of medical office building green upgrades from an owner/lessor perspective

Abstract: Purpose – The purpose of this paper is to exam the financial impact on the owner/lessor who is considering a partial energy upgrade to an existing medical office building. The owner who leases the building using a triple net lease does the upgrade prior to leasing the building, with the expectation of earning higher rents. How much should the owner who leases the property spend for a given rent per square foot increase? Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t Manoliadis et al (2006) in Greece. The finding also agrees with other researchers (Windapo, 2014;Brotman, 2016), who found that rising energy costs is the most important driving force behind green innovations implementation. Energy efficiency is indeed a high-priority in many developed countries (Pacheco et al, 2012).…”
Section: In the Us Andsupporting
confidence: 92%
“…A c c e p t e d M a n u s c r i p t Manoliadis et al (2006) in Greece. The finding also agrees with other researchers (Windapo, 2014;Brotman, 2016), who found that rising energy costs is the most important driving force behind green innovations implementation. Energy efficiency is indeed a high-priority in many developed countries (Pacheco et al, 2012).…”
Section: In the Us Andsupporting
confidence: 92%
“…Despite the appearance of a split incentive limiting investment in building energy efficiency, landlords indirectly benefit from investing in operational efficiencies that are passed on to tenants. This research strengthens the recent work ofBrotman (2016) and the early observation ofEichholtz et al (2010) that landlords are able to capitalize energy savings into higher net rental income; we find this holds no matter who receives the direct savings. Logistic models in both the Australia and US can be interpreted that the offer of operational savings may make a tenant more amenable to enter into a net lease agreement, suggesting Brotman's case study of medical offices is transferrable across markets and sectors.…”
supporting
confidence: 90%
“… Barrier/Anti-incentive Description Ref. Split incentives Particularly important in rental housings where interests of two parties conflict and neither the landlord (due to low ROI) nor the tenant (high initial costs) wants to invest in energy efficiency upgrade [ 119 , [196] , [197] , [198] ] Weak incentives Lack of attractive amount of incentive and connection between the government budget and the energy target needed to be achieved by FIs [ 9 , 11 , 197 , 199 ] Time of implementation Application of FIs at wrong time [ 200 ] Negative impacts of FIs interaction Mitigating impacts are negative interaction between two policy instruments that result in reduced savings [ [201] , [202] , [203] , [204] ] Behavioral impacts Low priority towards energy efficiency (Low resource consumption culture present in most developed countries makes it difficult for FIs to be successful) Free riders (Free-riders are consumers who would have performed energy upgrade regardless of introduction of FIs.) Non-takers (Non-takers are consumers who do not perform energy upgrade even with the introduction of FIs) Rebound effect (Rebound effect results in less energy savings compared to expected due to introduction of FIs and is a source of energy efficiency gap) [ 11 , 21 , 145 , 148 , 163 , 169 , 175 , 191 , 199 ] Other Barriers Tax exemptions High initial i...…”
Section: Effectiveness Of Financial Incentivesmentioning
confidence: 99%
“…This will offset the maximum possible sustainability targets. On the other hand, the application of utility rebate incentives during a buildings’ operation time will encourage the use of equipment to their full useful life and meet sustainable goals of equipment energy upgrade [ 200 ]. Sometimes an existing FI such as retrofitting incentives may become unattractive to a user due to reduced utility prices.…”
Section: Effectiveness Of Financial Incentivesmentioning
confidence: 99%
See 1 more Smart Citation